Consumer Segmentation and Purchase Behavior in the Frozen Beef Market: Optimizing Product Attributes for Sustainability-Oriented Marketing Strategies - I Putu Gede Didik Widiarta; Cori Qamara; Novemia Fatmarischa; Dani Nur Arifin; I Gede Arie Mahendra Putra; Made Hardinata Wijakesuma (SEAS (Sustainable Environment Agricultural Science), 2025)
The frozen beef market is experiencing significant growth, driven by urbanization, rising incomes, and increasing consumer demand for convenient, high-quality protein sources. This study investigates consumer segmentation and purchasing behavior in this market, focusing on optimizing product attributes for sustainability-oriented marketing strategies. A cross-sectional quantitative design was employed, utilizing online surveys to gather data from 385 valid respondents. K-means clustering identified three distinct consumer segments: price-oriented consumers (35%), quality-oriented consumers (45%), and sustainability-conscious consumers (20%). Price-oriented consumers, predominantly from low-income groups, prioritize affordability and product availability, showing limited concern for sustainability attributes. Quality-oriented consumers, typically middle-income, emphasize product quality, hygiene, and safety certifications in their purchasing decisions. Sustainability-conscious consumers, predominantly high-income individuals, prioritize eco-friendly packaging and certifications, demonstrating high involvement and willingness to pay a premium for sustainable products. Regression analysis revealed key factors influencing purchase behavior: price sensitivity for low-income consumers, product quality and safety certifications for middle-income consumers, and sustainability attributes for high-income consumers. Younger and more educated consumers were more responsive to sustainability, while older consumers placed more value on traditional attributes. These findings emphasize the need for targeted marketing strategies, including affordability-focused campaigns for price-sensitive consumers, quality-driven branding for mid-level buyers, and sustainability-focused messaging for eco-conscious consumers. The study also highlights the broader implications of promoting sustainable practices in meat production to align with global Sustainable Development Goals (SDGs) and the increasing consumer demand for ethical consumption